(untitled) (World Bulletin of Social Sciences, 2021)
At present, quality assurance of educational services is the main task of educational institutions. A variety of methods are used to assess the quality of education and efforts are made to improve it. This article provides information on the qualitative parameters of qualitative assessment of education and the science of qualimetry